The early age of national marching band contest - Suanmonta, Tawanchai (Linguistics and Culture Review, 2021)
This academic article aims to 1) study the history of the national marching band contest; 2) the development of the national marching band contest. The results showed that National Marching Band Contest has been held from 1982 until the present. The contest in the early age from 1982 to 1993 is divided into three categories: Category A, Men, Category B, Men and Women, Category C, Women. The winning marching band will receive a royal trophy. In addition, the marching band has to play three songs at the Supachalasai Stadium: royal song (Rama IX), Thai Thao song or Prelude song, and a selected song according to preference, continuing with the march music: sports ground music, and Thai Military Bank (TMB) song which is a compulsory one. The marching band contest has been developed because the contest management activity is an important factor in the development of standards for marching bands to grow rapidly at the national level from an early age to the present.